2021
DOI: 10.1159/000510032
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Triglyceride, Fatty Acid Translocase, and Toll-Like Receptor 4 and Lower Level of HDL-C in Pregnant Women with GDM and Their Close Correlation with Neonatal Weight

Abstract: <b><i>Objectives:</i></b> In this study, we aimed to compare the levels of maternal blood lipids, placental and venous blood lipid transporters, and inflammatory factor receptors in pregnant women with and without gestational diabetes mellitus (GDM). We also aimed to figure out the relationship between these values and neonatal weight. <b><i>Methods:</i></b> Fifty pregnant women with GDM under blood glucose control belong to the case group, and 50 pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Compared with insulin, glyburide was associated with higher neonatal BW, while metformin was with lower BW of infants, in which the results were the same as a previous study [14]. Zhou et al [61] suggested that the level of triglyceride in maternal blood was positively correlated with neonatal BW. Metformin is also confirmed to reduce the level of triglyceride in nonobese type 2 diabetes mellitus patients [62].…”
Section: Comparison With Other Studiessupporting
confidence: 80%
“…Compared with insulin, glyburide was associated with higher neonatal BW, while metformin was with lower BW of infants, in which the results were the same as a previous study [14]. Zhou et al [61] suggested that the level of triglyceride in maternal blood was positively correlated with neonatal BW. Metformin is also confirmed to reduce the level of triglyceride in nonobese type 2 diabetes mellitus patients [62].…”
Section: Comparison With Other Studiessupporting
confidence: 80%
“…There was also no difference in HDL between the groups analyzed. Other studies found low HDL levels and high triglyceride levels in patients with preeclampsia when compared to controls ( Dong et al, 2021 ; Zhou et al, 2021 ). In our study, triglyceride levels were higher in patients with preeclampsia than in the control group.…”
Section: Discussionmentioning
confidence: 86%
“…However, one unanticipated finding was that there was no significant difference between the intramuscular triglyceride contents in the chronic DMSO treatment group and the forskolin treatment group. This result may be explained by the hypothesis that a self-protection mechanism might be activated to prevent fatty acids from being hydrolyzed ( Zhou et al, 2021a ) when the intramuscular abundance of triglycerides was not elevated by external intervention, and further investigation is suggested to validate it.…”
Section: Discussionmentioning
confidence: 99%